Duty-Cycle Monitor / Adam Othman and Ahmad Yusuf Fadzil - Othman, Adam; Fadzil, Ahmad Yusuf (2003)
Assalamualaikum w.r.t.bt. Our project is “Duty-Cycle Monitor”. We choose this project because it has many application and important for everyone. This project is about become the solution to have a good frequency waveform when we are using the oscilloscope. This project is simple and can save our cost from bought another oscilloscope. It helps us to have a good and clean waveform. We hope it can help all of us to have a clean reading waveform. Wassalam.